2019
DOI: 10.1680/jgeot.17.t.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biofilm on gas permeability of unsaturated sand

Abstract: Microbial activities may sustainably improve earthen structures such as landfill covers. Typically, after consuming nutrient, bacteria produce hydrated exopolysaccharide to form a biofilm, which may cause bio-clogging in soil. Previous studies have mainly focused on the combined effects of biofilm and nutrient on the water permeability of saturated sand. The present study investigates biofilm effects on gas permeability of unsaturated sand at different degrees of saturation using a flexible wall permeameter. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Bioclogging is the clogging of pore space in porous media by the microbial biomass [10], resulting in reducing its hydraulic conductivity. The microbial biomass could be the bacterial cells and their productions, such as the biofilms (composed of approximately 80%-85% extracellular polymeric substance) [11,[87][88][89], and the precipitated calcium carbonate with MICP process shown in Eqs. ( 1)-( 4).…”
Section: Biocloggingmentioning
confidence: 99%
“…Bioclogging is the clogging of pore space in porous media by the microbial biomass [10], resulting in reducing its hydraulic conductivity. The microbial biomass could be the bacterial cells and their productions, such as the biofilms (composed of approximately 80%-85% extracellular polymeric substance) [11,[87][88][89], and the precipitated calcium carbonate with MICP process shown in Eqs. ( 1)-( 4).…”
Section: Biocloggingmentioning
confidence: 99%
“…Generally, soils with a coarser texture exhibit lower water-holding capacity than those with a finer texture. Several practices have been proposed to improve soil hydraulic properties, including using organic amendments, such as livestock manure, compost, plant residues, and biochar 12 15 . Studies have shown that these amendments can enhance water retention and flow within soils by impacting soil aggregation, pore size distribution, and water adsorption properties, owing to their high specific surface area and water-holding capacity.…”
Section: Introductionmentioning
confidence: 99%